How do leadership motives affect informal and formal leadership emergence?. (10th October 2012) - Luria, Gil; Berson, Yair
Summary To what extent and in what ways do leadership motives of potential leaders predict their informal and formal leadership assignments? To address these questions, we conducted two studies in a military setting. In the first study (n = 215), we examined a mediated‐moderation model in which we hypothesized that the motivation to lead (MTL) of candidates to an elite unit would predict their teamwork behaviors and their tendency to emerge as leaders of their peers. We further hypothesized that cognitive ability would interact with MTL to predict teamwork behaviors and that teamwork behaviors would mediate the relationship between this interaction and leadership emergence. In Study 2, we followed up 60 candidates who were selected to the unit and examined whether MTL would predict the extent to which they achieved formal leadership roles. The findings of Study 1 supported the hypotheses included in the moderated mediation model. In Study 2, as expected, MTL predicted formal leadership emergence. We discuss several theoretical implications of these findings. Copyright © 2012 John Wiley & Sons, Ltd.